Inter- and intra-household linkages between the informal and formal sector: a case study for Urban Burkina Faso - Michael Grimm; Isabel Günther (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Given the current focus of international development policy on pro-poor growth and poverty reduction, the role of the informal sector in the process of economic development is again at the top of the research and policy agenda. A key question is if pro-poor growth policies have to address the informal sector specifically and in any particular way or if the informal sector evolves like the rest of the economy and that therefore good growth policies are also good informal sector policies. Therefore, it is of crucial importance to understand the linkages – in quality and magnitude – between the informal sector and the rest of the economy. We argue that linkages between the formal and informal sector can exist on a macro as well as on a micro level. Empirically, we analyze both levels for urban areas in Burkina Faso using households as an observation unit. We show that in this country macro or inter-household linkages between the formal and informal economy are rather weak and that it is the performance of the whole economy in general which matters most for the informal sector. In contrast, micro or intra-household linkages between informal and formal labour supply and earnings seem more important and their understanding seems extremely useful when thinking about pro-poor growth strategies.
Keywords: D1; J2; O1; 330; informal labour market; dual economy; poverty; pro-poor growth; Informeller Sektor; Arbeitsmarkt; Dualökonomie; Armut; Burkina Faso